ENT 530 Social Media Portfolio: Dr Luxury Perfume / Samsiah Hassan A Gani - Hassan A Gani, Samsiah (2021)
DR Luxury Perfume is one of the best perfume’s brand. This is an online business that promote perfumes with variety scents and aroma such as floral and sweets fragrances. Furthermore, DR Luxury Perfume is more to natural fragrance as it is alcohol-free perfumes. We try to build up a business which will be known for product that is low prices with high quality in order to gain our customers. Also, we offered delivery service with ‘cash on delivery’ and online bank in for our customer. For our products, we also offer gift items, ladies and men’s collection, and combo collection. The business start operating on 2018 and start create own Facebook page to attract more customer. We have used a Facebook page as a platform to attract more customer. We have promoted our product by posting the teaser, hard sell and soft sell to gain customer awareness. For our products, customer from different background is welcome as our products is suitable for all. We have targeted teenagers and adults as our customer. Our product is a high-quality product and the aroma can compete with international perfume as it has long lasting scents. This shows that DR Luxury Perfume is a good choice for perfume’s brand and can keep growing in the market.